First clinical results of a personalized immunotherapeutic vaccine against recurrent, incompletely resected, treatment-resistant glioblastoma multiforme (GBM) tumors, based on combined allo- and auto-immune tumor reactivity. Issue 23 (28th May 2015) - Schijns, Virgil E.J.C.; Pretto, Chrystel; Devillers, Laurent; Pierre, Denis; Hofman, Florence M.; Chen, Thomas C.; Mespouille, Pascal; Hantos, Peter; Glorieux, Philippe; Bota, Daniela A.; Stathopoulos, Apostolos
Abstract: Glioblastoma multiforme (GBM) patients have a poor prognosis. After tumor recurrence statistics suggest an imminent death within 1–4.5 months. Supportive preclinical data, from a rat model, provided the rational for a prototype clinical vaccine preparation, named Gliovac (or ERC 1671) composed of autologous antigens, derived from the patient's surgically removed tumor tissue, which is administered together with allogeneic antigens from glioma tissue resected from other GBM patients. We now report the first results of the Gliovac treatment for treatment-resistant GBM patients. Nine (9) recurrent GBM patients, after standard of care treatment, including surgery radio- and chemotherapy temozolomide, and for US patients, also bevacizumab (Avastin™), were treated under a compassionate use/hospital exemption protocol. Gliovac was given intradermally, together with human GM-CSF (Leukine ® ), and preceded by a regimen of regulatory T cell-depleting, low-dose cyclophosphamide. Gliovac administration in patients that have failed standard of care therapies showed minimal toxicity and enhanced overall survival (OS). Six-month (26 weeks) survival for the nine Gliovac patients was 100% versus 33% in control group. At week 40, the published overall survival was 10% if recurrent, reoperated patients were not treated. In the Gliovac treated group, the survival at 40 weeks was 77%. Our data suggest that Gliovac has low toxicity and a promising efficacy. A phase II trial has recently been initiated in recurrent, bevacizumab naïve GBM patients (NCT01903330).